Simulation of the effects of land use changes in soil carbon dynamics in the Piracicaba river basin, São Paulo State, Brazil - Silveira, Andréa Maria; Victoria, Reynaldo Luiz; Ballester, Maria Victoria; Camargo, Plínio Barbosa de; Martinelli, Luiz Antonio; Piccolo, Marisa de Cássia (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this study was to test adequability of the CENTURY model to simulate the effects of land use changes on soil carbon content and net primary production to specific subtropical Brazilian environmental conditions. After parameterization, simulations were performed for forested areas, pasture and sugarcane cultures which have economical importance and representative areal extension in the Piracicaba River basin, São Paulo State, Brazil. The results obtained indicate that changes in use/cover from forest to agricultural practices resulted in lower soil carbon stocks. The simulations of the transition from forest to sugarcane indicated a decrease of 28% in soil carbon stocks for the first 12 years and 42% for 50 years of sugarcane cultivation. The simulation of the transition from forest to pasture and then to sugarcane resulted in a 24% loss of soil carbon stock for the first transition (forest-pasture) and of 22% for the second one (pasture-sugar-cane). The net primary production results obtained for forest (6.6 ton ha-1 yr-1), sugarcane (77, 82, 80 ton ha-1 yr-1) and pasture (6.5 ton ha-1 yr-1) were similar to those observed by other authors in field measurements.